Results of kinetostatic research of road energy harvesting system with slider-rocker mechanism - A. V. Prudiy; Yu. M. Lyashenko (Омский научный вестник)
The base factor of accidents with pedestrians is zero visibility as revealed by Russian auto statistic. Drivers have a poor view of pedestrians and crosswalk at twilight and night against road sign. Currently autonomous wind turbines and solar panels are used for improve of road safety. From another angle practice possibility of equipment type as road energy harvesting system is studying scientific collaboration. Operation of the systems is based on car motion energy conversion to electrical energy. The research goal is force determination acting in mechanism of road energy harvesting system. As a result of force study of road energy harvesting system, the forces in mechanical energy converter to electrical energy are determined when a car pass. On generator shaft torque is created equal 393 N∙m when typical car passes with 1600 kg mass by way road energy harvesting system from the performed calculations. Moreover, in generator resistive torque produces with value depending speed of moving car: at speed of 20 km/h the resistive torque is 115 N∙m; at speed of 30 km/h resistive torque is 260 N∙m; at speed of 40 km/h resistive torque is 390 N∙m. The energy amount saved by flywheel is directly proportional to speed and has values: at speed of 20 km/h energy is 47 J; at speed of 30 km/h energy is 105 J; at speed of 40 km/h energy is 165 J. The calculation data show that road energy harvesting system is operable with given parameters of construction elements.